PENGARUH MODEL TEACHING PERSONALITY SOCIAL AND RESPONSIBILITY DALAM MENINGKATKAN SIKAP TANGGUNG JAWAB: SYSTEMATIC LITERATURE REVIEW - Rian Muhamad Rizki; Lilis Komariyah; Alit Rahmat; Carsiwan Carsiwan (STKIP Melawi, 2024)
Abstract: This research aims to determine the effect of using the Teaching Personality Social and Responsibility (TPSR) learning model on the sense of responsibility of students in school. The research method used is Systematic Literature Review (SLR) with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and limits the search for articles to the last 10 years of publication in national and international journals that are openly accessible (open access). The results of the data identification show that the TPSR learning model has a significant effect on improving the sense of responsibility of students in school. Based on these results, the process of physical education learning in schools can be improved towards developing the sense of responsibility of students. Keywords: TPSR learning model, physical education, sense of responsibility. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan model pembelajaran Teaching Personality Social and Responsibility (TPSR) terhadap sikap tanggung jawab peserta didik di Sekolah. Metode penelitian ini menggunakan Systematic Literature Review (SLR) dengan menggunakan PRISMA (Preferred Reporting ItemsÂ for Systematic Reviews and Meta-Analyses) dan membatasi pencarian artikel pada rentang waktu publikasi 10 tahun terakhir yang diterbitkan pada jurnal nasional dan internasional yang dapat diakses secara terbuka (open access). Hasil identifikasi data menunjukkan bahwa model pembelajaran TPSR sangat berpengaruh terhadap peningkatan sikap tanggung jawab peserta didik di Sekolah. Berdasarkan hasil tersebut Proses pembelajaran Pendidikan Jasmani di Sekolah sudah dapat diperbaiki kearah yang lebih baik dalam mengembangkan sikap tanggung jawab peserta didik. KataKunci: Model pembelajaran TPSR, Pendidikan Jasmani, sikap tanggung jawab.